Why Residency Programs Should Not Ignore the Electronic Heath Record after Adoption - Krawiec, C (Perspect Health Inf Manag, 2019)
During residency training, one of the tools residents learn to use is the electronic health record (EHR). The EHR contains up-to-date medical data that are crucial to the care of the patient; thus the provider must know what is pertinent, where to locate it, and how to efficiently document the data for ongoing communication of patient care. Because institutions may have different EHR vendors, EHR workflow study data are often obtained in single institutions, with a limited number of participants and specialties. Increasing our understanding of the subtleties of residents' EHR usage not only can help educators understand how residents use the EHR but also may provide information on another cognitive factor to assess residents' performance. This, however, will only occur when EHR skills are considered an important part of residency training and we ask our EHR vendors to help us develop validated electronic tools to assess EHR performance.